Rejected tiles-type TL-1 - TL-2, supplying of 2nd consignment of tiles TL-1 and TL-2 and supplying 1st lot of tile type TL-6 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding rejected tiles and supplying of tiles for BRACU new campus project.